Antimicrobial/antibiofilm activity and cytotoxic studies of β-thujaplicin derivatives - Fotopoulou, Theano (2016)
Natural β-thujaplicin displays a remarkable array of biological activities for the prevention or treatment of various disorders while its tropolone scaffold inspired the synthesis of new analogs. The main goal of the current study was to evaluate the influence of 4-substituted piperazine moieties at position 7 of the β-thujaplicin scaffold, on the antimicrobial activity. In order to determine the biological activity of the β-thujaplicin derivatives, a microdilution method was used against a wide variety of bacteria and fungi. Pseudomonas aeruginosa PAO 1 was used for testing antiquorum and antibiofilm effects. Four human tumor cell lines (MCF-7, NCI-H460, HeLa, and HepG2) and a porcine liver derived cell line (PLP2) were used for testing antitumor and cytotoxic activity. The compounds present better antibacterial and antifungal activity in comparison with approved antimicrobials used as control agents. β-Thujaplicin showed strong antibacterial and antifungal activities against all tested species. Further studies of their antibacterial activity revealed that all compounds presented good antibiofilm and antiquorum effects. Fungi were more susceptible than bacteria to the tested compounds, with the exception of MK150, which possessed the best antibacterial effect. None of the tested compounds, at the GI50 values obtained for the tumor cell lines, have shown toxicity for non-tumor liver cells (PLP2). The prediction of physicochemical properties of the compounds was performed to further explain the structure-activity relationship. Finally, in order to explore a possible mechanism of action of the synthesized compounds, molecular docking studies were performed on CYP51 (14-a lanosterol demethylase), an important component of the fungal cell membrane.